Visions of the courtly body : the patronage of George Villiers, first Duke of Buckingham, and the triumph of painting at the Stuart Court - Hille, Christiane (Akademie Verlag, 2012)
"As the first comprehensive study of Buckingham's patronage of the visual arts, this book is concerned with the question of how the painted image of the courtier transferred strategies of social distinction that had originated in the masque to the language of painting. Establishing a new grammar in the competing rhetorics of bodily self-fashioning, this recast notion of portraiture contributed to an epistemological change in perceptions of visual representation at the early modern English court, in the course of which painting advanced to the central art form in the aesthetics of kingship." (cover - p. 4).